"There will be mushrooms again" – Foraging, landscape and forest fire. (March 2021) - Butler, Andrew; Ångman, Elin; Ode Sang, Åsa; Sarlöv-Herlin, Ingrid; Åkerskog, A.; Knez, Igor
Abstract: In this paper, we address the relevance of recreational foraging, picking berries and mushrooms, for developing connection to nature and what happens when that practice is interrupted by drastic landscape change. We use the site of the largest forest fire in modern Swedish history as a case to examining the relevance of foraging. In previous studies, positive associations have been observed between the activity of picking berries and mushrooms with landscape-identity prior to forest fires. The results suggest that the more participants enjoyed foraging, the stronger their attachment to the landscape as well as memories and reasoning about the landscape. These relationships remainedafter the area has been drastically altered by fire, implying a significant role of foraging for keeping "alive" the positive feelings and memories of the forest landscape. Through questionnaires and semistructured interviews, we examine why individuals forage, what foraging meant for them before the event and how they relate to the landscape and foraging after the fire. Our findings suggest that these connections are built on an interplay between place, practice and intimate knowledge. We conclude that foraging play an essential role in defining and developing connections to landscape which can act as the basis for stewardship of the landscape. Management implications: In order to facilitate reconnection to the landscape after a forest fire there is a need to understand how individuals and communities related to the landscape before the fire. Foraging will always be reliant on issues of access, and specific management regimes. Cultural values and small-scale activities play an essential role in defining and developing connections to landscape. Connections which can ultimately inform a sense of responsibility and stewardship. Activities such as foraging are reliant on more than just the affordance provided by the physical and visual character of a landscape. Management implications: To facilitate reconnection to landscape after a forest fire requires an understanding of the bonds before the fire. Foraging will always be reliant on issues of access, and specific management regimes. Small-scale activities play an essential role in developing connections to landscape, informing a sense of responsibility. Activities such as foraging are reliant on more than just the affordance provided by the physical character of landscape.